1998
DOI: 10.1097/00007890-199807150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Double-Blind, Randomized, Multicenter, Phase Iii Clinical Trial of Thymoglobulin Versus Atgam in the Treatment of Acute Graft Rejection Episodes After Renal Transplantation1,2

Abstract: Thymoglobulin was found to be superior to Atgam in reversing acute rejection and preventing recurrent rejection after therapy in renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
123
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(127 citation statements)
references
References 18 publications
1
123
1
2
Order By: Relevance
“…In the transplantations from an unrelated donor, the addition of low-dose corticosteroid to the GVHD prophylactic regimen Table 2 Characteristics of the patients with post-transplant lymphoproliferative disorder (PTLD) PTLD after non-T-cell-depleted stem cell transplantation E Juvonen et al consisting of cyclosporine and methotrexate may have been a further contributing factor, although in our earlier study in the sibling transplantation setting there were fewer infections in the group of patients given the triple prophylaxis compared to patients given the combination of cyclosporine and methotrexate. 19 The present study also suggests a difference in the immunosuppressive effect between the different ATG products in the doses used, which is in accordance with the previous study by Gaber et al 23 They showed that after renal transplantation, the degree of T-cell depletion caused by Thymoglobuline s was significantly greater and longerlasting when compared to the effects of Atgam s . Thymoglobuline s was also more effective in the treatment of acute rejection.…”
Section: Discussionsupporting
confidence: 91%
“…In the transplantations from an unrelated donor, the addition of low-dose corticosteroid to the GVHD prophylactic regimen Table 2 Characteristics of the patients with post-transplant lymphoproliferative disorder (PTLD) PTLD after non-T-cell-depleted stem cell transplantation E Juvonen et al consisting of cyclosporine and methotrexate may have been a further contributing factor, although in our earlier study in the sibling transplantation setting there were fewer infections in the group of patients given the triple prophylaxis compared to patients given the combination of cyclosporine and methotrexate. 19 The present study also suggests a difference in the immunosuppressive effect between the different ATG products in the doses used, which is in accordance with the previous study by Gaber et al 23 They showed that after renal transplantation, the degree of T-cell depletion caused by Thymoglobuline s was significantly greater and longerlasting when compared to the effects of Atgam s . Thymoglobuline s was also more effective in the treatment of acute rejection.…”
Section: Discussionsupporting
confidence: 91%
“…Four female RMs 10-13 years old received a single dose of 2 Gy TBI, 3 mg/kg tacrolimus, 1 mg/kg prednisone and 1Á5 mg/kg anti-thymocyte globulin intravenously (thymoglobulin rabbit ATG; Genzyme, Cambridge, MA, USA). Preville et al calculated that a dose of 1 mg/kg in cynomolgus macaques was sufficient to induce borderline immunosuppressive effects, while a dose of 5 mg/kg reflects ATG used in organ transplantation [17,54,55].…”
Section: Animals and Sample Collectionmentioning
confidence: 99%
“…Early 7-to 10-d induction course with polyclonal antilymphocyte globulin or horsederived polyclonal anti-human thymocyte globulin has contributed to reduce the rate of acute rejection and improve early graft function in kidney transplant recipients (6,7). Even better results as far as frequency and severity of rejection episodes then were achieved with rabbit-derived polyclonal anti-human thymocyte globulin (RATG) (8), which thereafter became the standard biologic agent for induction therapy in kidney transplantation (9).…”
mentioning
confidence: 99%